Examine solid waste management practices: a case study at KDEB waste management, Selangor - Mohamed, Nazratulshima (2022)
This paper presents the current status of the solid waste management system in the State of Selangor by KDEB Waste Management. This study provides an overview by focusing on the performance of KDEBWM from the aspects of i) Identifying the waste management system in Selangor ii) To understand the population's pressure on waste generation and the amount of waste produced iii) Knowing the factors that interfere with the performance of KDEB Waste Management in terms of finances, population attitudes, equipment, and economic factors. Information obtained from 11 participants, namely three KDEB Waste Management staff at the headquarters, and 8 selected branch respondents consisting of branches at the District Council, Municipal Council and City Council through the interview method. Therefore, to achieve the objective, both primary and secondary data sources are used. Primary data was collected through questionnaires, interviews, and observations in the field. While secondary data is extracted from different published and unpublished materials. In addition, identify the main problems and limitations that prevent improvement in current solid waste management practices and there are recommendations on the steps that need to be taken to reduce these problems. Future studies need to take into account a larger sample size, holding discussions with other sectors.